Gingival state and presence of red complex bacteria in 12-year-old schoolchildren = Estado gingival y presencia de bacterias del complejo rojo en escolares de 12 años - Vega Chin, Alberto 1991-; Silva de la Fuente, Sandra María 1956-; Gómez Fernández, Adrián José 1980-; Ortiz Acuña, Lucía 1997-; Mora González, Alexa 1995- (2022)
The objective of this study was to determine the gingival state and presence of red complex bacteria in saliva samples of 12-year-old schoolchildren. A calibrated periodontist evaluated biofilm index (BI) (Silness and Löe, 1964), presence of calculus, and gingival index (GI) (Silness and Löe, 1967) in sixty two 12-year-old students of Carmen Lyra School. Saliva samples were collected from each student. The DNA of each sample was extracted and amplified by the polymerase chain reaction (PCR) technique, using specific primers. The BI was 1.18. Calculus was present in 40.40% of the schoolchildren examined; 19.4% was supragingival calculus and 21% both supragingival and subgingival calculus. The GI was 0.97, which according to Silness and Löe is mild gingivitis. Gingivitis was present in 96.8% of the children examined. Regarding the PCR tests: 18 of the samples (31.58%) did not present any of the bacteria analyzed and the remaining 39 samples (68.42%) were positive for at least the presence of red complex bacteria. Within the limitations of this study, it is concluded that the prevalence of gingivitis and calculus is high in the sample examined, and the gingival state observed in the study population, may be related to the presence of red complex bacteria.
El objetivo de este estudio era determinar el estado gingival y la presencia de bacterias del complejo rojo en muestras de saliva de niños de 12 años de la Escuela Carmen Lyra. Una periodoncista calibrada evaluó en 62 estudiantes de 12 años de la Escuela Carmen Lyra, el índice de biofilme (IB) (Silness y Löe, 1964), la presencia de cálculo y el índice gingival (IG) (Silness y Löe, 1967). Se recolectaron muestras de saliva de cada estudiante. El ADN de cada muestra fue extraído y amplificado por medio de la prueba PCR, empleando primers específicos, para determinar la presencia de bacterias del complejo rojo. El IB fue de 1.18. El cálculo estuvo presente en el 40.40% de la muestra, se encontró 19.4% de cálculo en supragingival y 21% tanto en supragingival como en subgingival. El IG fue de 0.97, que de acuerdo con Silness y Löe es una gingivitis leve. La gingivitis estuvo presente en el 96.8 % de los niños examinados. Con respecto a las pruebas PCR: 18 de las muestras (31.58 %) no presentaron ninguna de las bacterias analizadas y las 39 muestras restantes (68.42 %) fueron positivas por lo menos a la presencia de las bacterias del complejo rojo.Dentro de las limitaciones de este estudio, se concluye que la prevalencia de gingivitis y cálculo es alta en la muestra examinada y el estado gingival observado puede estar relacionado con la presencia de bacterias del complejo rojo.
En revista Odóvtos, vol. 24, no. 3 (septiembre-diciembre 2022)
Descripción basada en el contenido visto el 05 de diciembre, 2024
También disponible en formato HTML y EPUB